Acceptance and Compassion-Based Therapy Targeting Shame in Body Dysmorphic Disorder: A Multiple Baseline Study. Issue 3 (May 2023) - Linde, Johanna; Luoma, Jason B.; Rück, Christian; Ramnerö, Jonas; Lundgren, Tobias
Shame is considered central in body dysmorphic disorder (BDD) and empirical accounts highlight the link between shame and BDD symptoms as well as common negative psychosocial effects of the disorder, yet there is a lack of interventions addressing shame in this context. In the past decade, Acceptance and commitment therapy (ACT) and interventions that foster self-compassion have shown promise for reducing the negative effects of shame in a range of clinical problems. The aim of the present study was to develop and evaluate an acceptance and compassion-based treatment specifically targeting shame in BDD. Using a randomized nonconcurrent multiple baseline design, the 12-session intervention, ACT with Compassion (ACTwC), was examined in a psychiatric outpatient sample of five adults diagnosed with BDD. The daily ratings showed marked reductions in BDD-behaviors and self-criticism at posttreatment for four of five participants, while three participants demonstrated decreases in body shame compared to baseline. Improvements were maintained at 6-months follow-up. The intervention also led to reliable long-term improvements in general shame, overall BDD-symptoms, depressive symptoms, and quality of life for four of five participants. All treatment responders showed significant gains in psychological flexibility and self-compassion. Participants reported high credibility and satisfaction with the treatment. These preliminary results suggest that ACTwC may be a promising approach to treating shame in BDD, worthy of further investigation.